2021
DOI: 10.3389/fsufs.2021.672981
|View full text |Cite
|
Sign up to set email alerts
|

Socioecological Factors and Farmer Perceptions Impacting Pesticide Use and Pollinator Conservation on Cucurbit Farms

Abstract: While research suggests that pollinator decline is linked with agricultural practices, it is unclear whether farmers share this view and adapt management to promote pollinators based on their understanding of these threats. To address these issues, we surveyed farmers of pollinator-dependent cucurbit crops across four states in the Midwest, USA. We grouped farmers by their perceptions of pollinator declines and routes of pesticide exposure and used statistical models to evaluate if farmers manage pests and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…Limitations in sample size ( n = 85) also influenced cluster membership, indicating a tradeoff in allowing for variation in beliefs and statistical inference. While greedier solutions increase cluster membership (Bloom et al, 2021), correlations between beliefs and practices may be obscured. More broadly, to parallel previously understood variation in the practices used on organic farms (e.g., a spectrum of conventionalization across organic farms), we suggest there also exists variation in beliefs, and allowing for this variation, while limiting in some regards (e.g., low membership groupings), promotes the untangling of correlations between beliefs and farming practice adoption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations in sample size ( n = 85) also influenced cluster membership, indicating a tradeoff in allowing for variation in beliefs and statistical inference. While greedier solutions increase cluster membership (Bloom et al, 2021), correlations between beliefs and practices may be obscured. More broadly, to parallel previously understood variation in the practices used on organic farms (e.g., a spectrum of conventionalization across organic farms), we suggest there also exists variation in beliefs, and allowing for this variation, while limiting in some regards (e.g., low membership groupings), promotes the untangling of correlations between beliefs and farming practice adoption.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Bloom et al (2021) found that demographics and farming system characteristics regulated practice adoption, but beliefs were linked with participation in future conservation programs on farms. Thus, we constructed simple linear models to examine if motivation to adopt a new practice that supports pest-suppressive soil microbes would depend on farmer beliefs (Table S3 Q11).…”
Section: Methodsmentioning
confidence: 99%
“…Another possible way beekeepers might influence changes in agricultural strategies is by indirect contact, engaging with crop-based farmers that rely on pollination services for productivity. Studies investigating farmer perception on pollinator declines and supporting management strategies found that knowledge of the threats and the willingness to enact change was related to on-farm experiences and age (Bloom et al, 2021) rather than their use of managed pollinators, and was also linked to their level of knowledge on the subject (Osterman et al, 2021). Still, no studies were found on the perception of crop farmers on the topic of pollinator conservation and their level of engagement with beekeepers, so the possibility exists that beekeepers may well be able to interact as intermediaries between farmers and wild pollinator conservation strategies, providing education to crop farmers by simple interaction.…”
Section: Beekeeper Drive and Public Motivationmentioning
confidence: 99%
“…These advanced techniques can be incorporated into routine pollinator surveys to accelerate pollinator diversity research, offering deeper evolutionary insights for ecological analysis and conservation planning. Lastly, farmers, as stakeholders and landowners in agroecosystems, play important roles in pollinator conservation programs (Bloom et al, 2021); yet, their involvement has been minimal. Strengthening their engagement is crucial for a successful and cohesive pollinator protection strategy, requiring both governmental and NGO support, although a comprehensive strategy for this purpose is still lacking in China.…”
Section: Proposed Strategies For Pollinator Conservation In Agroecosy...mentioning
confidence: 99%